Regeneration and Agrobacterium-mediated genetic transformation of twelve Eucalyptus species - Tingting Zhou; Ying Lin; Yan Lin; Jianzhong Luo; Jihua Ding (Forestry Research, 2022)
Eucalyptus is a genus of over 900 species and hybrids, and many of them are valuable fast-growing hardwoods. Due to its economic importance, Eucalyptus is one of the early tree species whose genomes were deciphered. However, the lack of efficient genetic transformation systems severely restricts the functional genomic research on the plant. The success of Eucalyptus regeneration and transformation depends greatly on the genotypes and explants. In this study, we systematically screened 26 genotypes from 12 Eucalyptus species in an attempt to obtain Eucalyptus genotypes with high regeneration potential. We developed two common regeneration media that can be applied to most tested Eucalyptus genotypes for both seeding hypocotyls and cloned internodes as explants. We then implemented DsRed2 as a visual marker for genetic transformation efficiency test. Our results suggest that E. camaldulen and E. robusta are amenable for genetic transformation. Finally, we successfully set up a stable Agrobacterium-mediated genetic transformation procedure for both E. camaldulen and E. robusta using seeding hypocotyls and cloned internodes respectively. Taken together, our study provides valuable means for vegetative propagation, gene transformation, CRISPR based gene mutagenesis, activation and suppression, as well as functional characterization of genes in Eucalyptus.